Values of Baseline Posterior Circulation Acute Stroke Prognosis Early Computed Tomography Score for Treatment Decision of Acute Basilar Artery Occlusion. Issue 3 (11th February 2021) - Sang, Hongfei; Li, Fengli; Yuan, Junjie; Liu, Shuai; Luo, Weidong; Wen, Changming; Zhu, Qiyi; Chen, Wenhuo; Lin, Min; Qi, Li; Zhong, Yaoyi; Wang, Zhen; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: This study aimed to analyze the impact of baseline posterior circulation Acute Stroke Prognosis Early Computed Tomography Score (pc-ASPECTS) on the efficacy and safety of endovascular therapy (EVT) for patients with acute basilar artery occlusion. Methods: The BASILAR was a nationwide prospective registry of consecutive patients with a symptomatic and radiologically confirmed acute basilar artery occlusion within 24 hours of symptom onset. We estimated the effect of standard medical therapy alone (SMT group) versus SMT plus EVT (EVT group) for patients with documented pc-ASPECTS on noncontrast CT, both as a categorical (0–4 versus 5–7 versus 8–10) and as a continuous variable. The primary outcomes included favorable functional outcomes (modified Rankin Scale ≤3) at 90 days and mortality within 90 days. Results: In total, 823 cases were included: 468 with pc-ASPECTS 8 to 10 (SMT: 71; EVT: 397), 317 with pc-ASPECTS 5 to 7 (SMT: 85; EVT: 232), and 38 with pc-ASPECTS 0 to 4 (SMT: 13; EVT: 25). EVT was associated with higher rate of favorable outcomes (adjusted relative risk with 95% CI, 4.35 [1.30–14.48] and 3.20 [1.68–6.09]; respectively) and lower mortality (60.8% versus 77.6%, P =0.005 and 35.0% versus 66.2%, P< 0.001; respectively) than SMT in the pc-ASPECTS 5 to 7 and 8 to 10 subgroups. Continuous benefit curves also showed the superior efficacy and safety of EVT over SMT in patients with pc-ASPECTS ≥5. Furthermore, the prognostic effect of onset to puncture time on favorable outcome with EVT was not significant after adjustment for pc-ASPECTS (adjusted odds ratio, 0.98 [95% CI, 0.94–1.02]). Conclusions: Patients of basilar artery occlusion with pc-ASPECTS ≥5 could benefit from EVT. The baseline pc-ASPECTS appears more important for decision making and predicting prognosis than time to EVT. Registration: URL: http://www.chictr.org.cn . Unique identifier: ChiCTR1800014759.